Retrospective analysis of clinicopathological characteristics of 19 ovarian juvenile granulosa cell tumor cases. Issue 7 (27th April 2021) - Ndhlovu, Elijah; Liu, Lili; Dai, Jun; Dong, Xiyuan; Zhang, Wen; Chen, Biao
Abstract: Aim: To describe the clinical and pathological characteristics, diagnosis, treatment, and outcomes of juvenile granulosa cell tumor (JGCT). Methods: We retrospectively analyzed the data of 19 patients with histopathologically confirmed juvenile granulosa cell tumors treated in two medical centers in Wuhan city of China between 1999 and 2019. Results: Totally, 19 patients were included during the period. The median age at diagnosis was 8.25 years (range, 0.25–28 years). The most common clinical presentation was abdominal pain, five out of 10 prepubertal children presented with precocious puberty. Three patients underwent radical surgery (including total hysterectomy, bilateral salpingo‐oophorectomy, omentectomy, and pelvic and para‐aortic lymphadenectomy), the other 16 patients had fertility‐sparing surgery (cystectomy or ipsilateral salpingo‐oophorectomy with or without omentectomy and lymphadenectomy). Eighteen patients had the international federation of gynecology and obstetrics (FIGO) stage I tumors, one patient had FIGO stage II disease. Twelve patients received postoperative adjuvant chemotherapy. The median follow‐up time from the time of diagnosis was 35 months (range, 13–250 months). One patient experienced relapse and died of the disease 32 months after the initial diagnosis. Eighteen patients were alive and had not experienced recurrence during the follow‐up period. The reproductive age patients that received fertility‐sparing surgery had regular menstruation. Conclusions: A majority of JGCTs are diagnosed as FIGO stage I tumors and have favorable clinical outcomes. Adjuvant chemotherapy seems to improve outcomes for patients with advanced‐stage JGCTs; however, the value of chemotherapy in stage Ic patients is still unknown. Fertility sparing surgery should be considered in young patients who wish to bear children.